A survey on commercial fish feed used at Fulpur area in Mymensingh district - Alam, M K; Habib, M A B; Tahmid, M S (Journal of the Bangladesh Agricultural University, 2012)
This study was performed in Fulpur upazila under Mymensingh district for the period of 13 months from August 2010 to August 2011 to know the socio-economic and aquaculture status of fish farm owners and to assess the nutritive value of commercial fish feed available at Fulpur upazila of Mymensingh district. Fish farm owners were prominent in the study area and majority was illiterate but had the ability of signature. The monoculture and polyculture farm in the studied area were established in ranged from 1995 to 2005, respectively. Most of the fish farm owners followed polyculture system and had small farm area. Majority of fish farm owners leased water body for aquaculture. The minimum size of the farm was 0.162 ha and maximum size of the farm was 3.722 ha. The average depth of the water body in winter season was 1.61 meter and in summer season was 2.32 meter. Majority of fish farm owners followed proper pre-stocking and post stocking management with maintaining high stocking density of fish and using either commercial or farm made fish feed. Among the commercial fish feed tested the highest value of moisture was found in Aftab feed, protein in Nourish feed, lipid in CP feed, ash in Aftab feed, fibre in ACI feed and carbohydrate in ACI feed. Most of the commercial fish feed maintain standard level of chemical composition. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12111 J. Bangladesh Agril. Univ. 10(1): 175178, 2012